Navigating Borders Inside Perspectives on the Process of Human Smuggling into the Netherlands - van Liempt, Ilse (IMISCoe Dissertations, 2007)
Navigating Borders into the Netherlands provides a unique in-depth look at human smuggling processes. Based on biographical interviews with smuggled migrants in the Netherlands, the study reveals considerable differences that exist in smuggling's underlying causes, how journeys evolve, and outcomes of the process. This research from an insider's perspective clearly demonstrates that smuggled migrants are not passive actors, there is a broad variety in types of smugglers, and interactions between migrants and smugglers largely determine how the smuggling process evolves.